Everyday Context Attenuates the Attentional Capture by Modern Threatening Stimuli. (February 2020) - Takeno, Masae; Kitagami, Shinji
Threatening stimuli such as snakes typically draw attention. This attentional bias, called the threat-superiority effect, is proposed as the response of a fear module that human beings evolved to detect specific threatening stimuli. Alternatively, the relevance-detection hypothesis proposes that the threat-superiority effect by modern threats (i.e., weapons) is induced when the threatening stimulus is the most relevant for circumventing danger in the context. Although previous studies have shown that an urban context enhanced the modern threat-superiority effect, these do not clarify whether the context induced the attentional bias or facilitated the response via the fear module. Therefore, the present study investigated whether weapons captured attention in a daily context where the weapons were typically used as tools. The results indicated that weapons in the usual context did not capture attention. It is supported that the modern threat-superiority effect depends on the context, as suggested by the relevance-detection hypothesis.